2007
DOI: 10.1016/j.bbrc.2007.06.188
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase induces Akt phosphorylation via a lipid raft receptor

Abstract: The endoglycosidase heparanase is the predominant enzyme that degrades heparan sulfate side chains of heparan sulfate proteoglycans, activity that is strongly implicated in tumor metastasis. Apart of its well characterized enzymatic activity, heparanase was noted to exert also enzymatic-independent functions. Among these is the induction of Akt/PKB phosphorylation noted in endothelial- and tumor-derived cells. Protein domains of heparanase required for signaling were not identified to date, nor were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 35 publications
3
56
0
Order By: Relevance
“…Binding studies with heparanase have suggested that a high affinity binding site for heparanase exists on many cell types and strongly support the existence of a specific heparanase receptor(s) (11,14). Several key features of the mechanism of AKT activation triggered by the putative receptor were identified in the present study.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Binding studies with heparanase have suggested that a high affinity binding site for heparanase exists on many cell types and strongly support the existence of a specific heparanase receptor(s) (11,14). Several key features of the mechanism of AKT activation triggered by the putative receptor were identified in the present study.…”
Section: Discussionsupporting
confidence: 74%
“…Evidence indicates that this receptor(s) is localized to lipid rafts, based on the inhibitory effect of cholesterol-depleting agents on heparanase signaling (14). Different proteins that have been suggested as heparanase receptors include mannose 6-phosphate receptor and low density lipoprotein receptor-related protein (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,35 Heparanase has also been shown to exert non-enzymatic effects, including phosphorylation of a number of factors. 36,37 Its translocation to the nucleus in various cell types may be an additional, potential, mechanism affecting gene transcription. 38 We have documented a biphasic gain of heparanase expression during liver regeneration following 70% PHx.…”
Section: Figurementioning
confidence: 99%
“…[31][32][33] The significance of this observation critically emerges from recent studies showing that secreted heparanase augments signal transduction pathways, leading to activation of certain protein kinases (that is, Akt, Src, EGFR) and increased gene transcription (that is, VEGF, TF, COX2) associated with enhanced tumor progression. 21,28,[34][35][36][37][38][39] Previous studies have shown that heparanase also assumes nuclear localization, 40,41 and that nuclear heparanase is associated with a favorable prognosis of head and neck, gastric, and esophageal cancer patients. 20,[41][42][43] It was unclear, however, at what stage of tumor initiation/progression nuclear translocation takes place.…”
Section: Discussionmentioning
confidence: 99%